PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MODEL PROBLEM BASED LEARNING PADA MATERI PROGRAM LINEAR KELAS XI SMA/MA - Ataya Aufa Saleh (Departemen Matematika, 2021)
Based on curriculum 2013, teaching materials should be able to facilitate students to beactive in learning process. However, in reality, the teaching materials used by the teacher are not accordance yet with curriculum 2013. There are no questions that can guide students to find theorems or principles of the topic. This research aims to develop a valid and practice student worksheet based on problem based learning model. By using this model, we expect students can involve in learning process actively.This research uses the Plomp development model. It has three phase, these are preliminary research phase, development or prototyping phase, and assessment phase. The research subjects were students of grade XI. The techniques of collecting data are observation, interviews and questionnaires. Questionnaire data were analyzed by descriptive statistics. While the data from observations and interviews were analyzed by descriptive techniques. The results of research that we obtain are valid and practice student worksheet. Based on content aspect, percentage value of student worksheet validity is 86,2% which is in very valid category. Meanwhile based on linguistic aspect,percentage value of student worksheet validity is 97,23% which is also in very valid category.Furthermore, the student worksheet is practical because they can be used easily by students. The percentage practicality of LKPD is 94% which is in the very practical category. Keywords -Student Worksheet, Problem Based Learning Model, Linear Programming